COMPUTER TEACHING MATERIALS AS A WAY OF IMPLEMENTING AN INDIVIDUAL APPROACH - Drach, A.S. (Pedagogy of Higher and Secondary Education, 2008)
The article is devoted to the actual problem of computer technology usage and the possibilities of their integration into the studying process. This usage favours the effectiveness in the solution of deductive aims. The author also determines the expediency and specific character of computer usage during the test control.